MOF-derived porous ZnO nanocube assembled fiber as well as preparation method and application thereof

By combining MOF and electrospinning technology, highly ordered porous ZnO nanocube assembled fibers were prepared, which solved the problem of agglomeration of existing materials during the calcination process and significantly improved its gas sensing performance.

CN119332372APending Publication Date: 2025-01-21ANHUI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411536501.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing MOF-derived porous ZnO nanocubes are prone to spontaneous agglomeration during calcination, resulting in low porosity and low specific surface area, limiting their application in gas detection performance.

Method used

By combining MOF and electrospinning technology, a tightly arranged interconnected fiber network of ZIF-8-derived porous ZnO nanocubes was prepared to form highly ordered nanocube assembled fibers.

Benefits of technology

It improves the surface area and pore rate of the material, significantly improves the gas -sensitive sensing performance of volatile organic pollutants, and provides rich active sites, and improves the sensitivity of gas detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332372A_ABST
    Figure CN119332372A_ABST
Patent Text Reader

Abstract

The invention provides an MOF (Metal Organic Framework)-derived porous ZnO nanocube assembled fiber as well as a preparation method and application thereof. The preparation method of the fiber comprises the following steps: preparing a ZIF-8 nanocube; performing electrostatic spinning on the ZIF-8 nanocube to obtain a precursor fiber; and calcining the precursor fiber, so as to obtain the fiber assembled by the MOF-derived porous ZnO nanocubes. On the basis that traditional MOF-derived porous ZnO nanocubes are extremely easy to agglomerate and disorderly after being calcined, so that the improvement of the gas-sensitive property is limited, a novel fiber network material in which ZIF-8-derived porous ZnO nanocubes are closely arranged and interconnected is constructed, and the novel fiber network material has a highly ordered structure, so that the specific surface area is greatly increased, the rich porosity is obtained, and the gas-sensitive property is improved. Therefore, the sensitivity of volatile organic pollutants can be effectively improved; in addition, the preparation method of the fiber provided by the invention is a universal and expansible method, and can be popularized to preparation and application of other MOFs-derived porous oxide nano-structure assembled fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a MOF-derived porous ZnO nanocube assembled fiber and a preparation method and application thereof. Background Art

[0002] Volatile organic pollutants are organic compounds that are volatile at room temperature and can enter the human body through the respiratory tract, digestive tract and skin. Long-term exposure to volatile organic pollutants can cause various health problems, such as headaches, nausea, vomiting, and in severe cases, may even lead to convulsions, coma and memory loss. Therefore, early monitoring of various volatile organic pollutant gases is crucial.

[0003] In recent years, metal oxide-based resistive gas sensors have been regarded as promising candidates for detecting volatile organic compounds due to their low price, high sensitivity, good portability, short response time, and high stability. However, an effective way to improve the sensing performance is to design and construct nanomaterials with special morphology and porous specific surface area. Calcination of metal organic framework precursors is a practical method to prepare porous metal oxides with controllable shape and composition. Metal organic framework (MOF)-derived metal oxides are used in gas sensing research due to their adjustable morphology, customizable pore structure, high specific surface area, and sufficient porosity. However, the existing MOF-derived porous ZnO nanocube structures are prone to spontaneous agglomeration during the calcination process, resulting in low porosity and low specific surface area as well as uneven material distribution when preparing sensors, which limits their application in gas detection performance. Summary of the invention

[0004] Based on the above technical problems, the present invention provides a MOF-derived porous ZnO nanocube assembled fiber and a preparation method and application thereof. By combining MOF and electrospinning technology, a new fiber network of ZIF-8-derived porous ZnO nanocubes tightly arranged and interconnected is constructed.

[0005] Compared with the disordered state of traditional MOF-derived porous ZnO nanocubes, MOF-derived porous ZnO nanocube assembled fibers have a highly ordered structure, which can greatly increase the specific surface area of ​​the material and obtain rich porosity, thus effectively improving the gas sensing performance of volatile organic pollutants.

[0006] In addition, the preparation method of ZIF-8-derived porous ZnO nanocube assembled fibers is a universal and scalable method, which can be extended to the preparation and application of other MOFs-derived porous oxide nanostructure assembled fibers: for example, ZIF-8 and gold are spun together to prepare MOF-derived porous Au-ZnO nanocube assembled fibers. MOFs can be diverse, and HKUST-1-derived porous CuO nanocube assembled fibers have been prepared.

[0007] The present invention provides a method for preparing a MOF-derived porous ZnO nanocube assembled fiber, comprising the following steps:

[0008] S1, preparation of ZIF-8 nanocubes;

[0009] S2, electrospinning the ZIF-8 nanocubes to obtain precursor fibers;

[0010] S3, calcining the precursor fiber to obtain the MOF-derived porous ZnO nanocube assembled fiber.

[0011] Preferably, step S1 specifically comprises: adding hexadecyltrimethylammonium bromide and zinc nitrate into water and dispersing them uniformly, and then adding them into an aqueous solution of 2-methylimidazole to react at room temperature, so as to obtain the ZIF-8 nanocubes;

[0012] Preferably, the molar ratio of hexadecyltrimethylammonium bromide, zinc nitrate and 2-methylimidazole is 0.01:0.5-2:40-70.

[0013] Preferably, the particle size of the ZIF-8 nanocubes is 250-300 nm.

[0014] Preferably, step S2 specifically comprises: adding the ZIF-8 nanocubes and polyacrylonitrile into an organic solvent and dispersing them uniformly, and then performing electrostatic spinning to obtain the precursor fiber;

[0015] Preferably, the organic solvent is N,N-dimethylformamide or tetrahydrofuran.

[0016] Preferably, the mass ratio of the ZIF-8 nanocubes to polyacrylonitrile is 1:1-3;

[0017] Preferably, the ZIF-8 nanocubes are dispersed in an organic solvent at a concentration of 0.1-0.3 g / mL.

[0018] Preferably, in step S2, in the electrospinning, the needle tube advancement speed is 0.0001-0.001 mm / s, the distance between the needle tip and the collector is 10-20 cm, the spinning voltage is 10-20 kV, and the relative humidity of the environment is 20-40% RH.

[0019] Preferably, in step S3, during the calcination treatment, the calcination temperature is 500-600°C, the time is 40-100 min, and the heating rate is 1-5°C / min.

[0020] The present invention also provides a MOF-derived porous ZnO nanocube assembled fiber, which is prepared by the above preparation method.

[0021] The present invention also proposes an application of the MOF-derived porous ZnO nanocube assembled fiber in a gas sensor.

[0022] Preferably, the gas sensor is used to detect n-butanol.

[0023] Beneficial effects:

[0024] (1) The present invention uses electrospinning technology to prepare ZIF-8 nanocubes into nanofiber precursors, and then prepares a series of MOF-derived porous ZnO nanocube assembled fibers with different diameters in air calcination, which form a unique network structure, high specific surface area, and rich porosity; compared with the disordered state of traditional MOF-derived porous ZnO nanocubes, MOF-derived porous ZnO nanocube assembled fibers have a highly ordered structure that can effectively improve the adsorption capacity of volatile organic pollutants, provide abundant active sites, and improve the sensitivity of gas detection, thereby improving the sensing performance of volatile organic pollutants.

[0025] (2) In the present invention, since the ZnO nanocubes themselves have a porous structure, the porous ZnO nanocubes obtained after high-temperature calcination can still maintain the shape formed before calcination, and the particle size after calcination is also controlled at about 250-300nm. At the same time, the electrostatic spinning technology greatly prevents the ZIF-8 nanocubes from agglomerating during the calcination process and uniformly disperses them, which can increase the adsorption specific surface area and improve the sufficient porosity. Therefore, the nanomaterial prepared by the preparation method of the present invention has a significant improvement effect on the sensitivity of the sensor.

[0026] (3) When the electrospinning technology is used in the present invention, when other polymers other than polyacrylonitrile are used as spinning carriers, the MOF-derived porous ZnO nanocube assembled fiber structure cannot be obtained. This may be because other polymers cannot effectively disperse the ZIF-8 nanocubes and cannot prevent the ZIF-8 nanocubes from agglomerating during the calcination process.

[0027] (4) The nano-ZnO material of the present invention is cheap and easy to obtain, has low preparation cost, and the product is easy to promote.

[0028] (5) The method for preparing ZIF-8-derived porous ZnO nanocube assembled fibers of the present invention is a universal and scalable method, which can be extended to the preparation and application of fibers assembled from porous oxide nanostructures derived from other MOFs. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 These are scanning electron microscope images of the porous ZnO nanocubes or porous ZnO nanocube-assembled fibers derived from MOF described in Comparative Example 1 and Example 3 of the present invention before and after calcination, wherein (a) is a scanning electron microscope image of the porous ZnO nanocubes derived from MOF described in Comparative Example 1 before calcination; (b) is a scanning electron microscope image of the porous ZnO nanocubes derived from MOF described in Comparative Example 1 after calcination; (c) is a scanning electron microscope image of the porous ZnO nanocube-assembled fibers derived from MOF described in Example 3 before calcination; (d) is a scanning electron microscope image of the porous ZnO nanocube-assembled fibers derived from MOF described in Example 3 after calcination;

[0030] Figure 2 The present invention is a scanning electron microscope image of the porous ZnO nanocube-assembled fibers derived from MOF described in Examples 1-5, wherein (a) is a scanning electron microscope image of the porous ZnO nanocube-assembled fibers derived from MOF described in Example 1; (b) is a scanning electron microscope image of the porous ZnO nanocube-assembled fibers derived from MOF described in Example 2; (c) is a scanning electron microscope image of the porous ZnO nanocube-assembled fibers derived from MOF described in Example 3; (d) is a scanning electron microscope image of the porous ZnO nanocube-assembled fibers derived from MOF described in Example 4; (e) is a scanning electron microscope image of the porous ZnO nanocube-assembled fibers derived from MOF described in Example 5;

[0031] Figure 3 X-ray single crystal powder diffraction patterns of the MOF-derived porous ZnO nanocube assembled fibers or porous ZnO nanocubes described in Examples 1-4 of the present invention and Comparative Example 1;

[0032] Figure 4 The specific surface area and pore size test graphs of the porous ZnO nanocube assembled fibers derived from MOF described in Example 3 of the present invention and the porous ZnO nanocubes derived from MOF described in Comparative Example 1, wherein (a) is a specific surface area test graph of the porous ZnO nanocube assembled fibers derived from MOF described in Example 3 and the porous ZnO nanocubes derived from MOF described in Comparative Example 1; (b) is a pore size test graph of the porous ZnO nanocube assembled fibers derived from MOF described in Example 3 and the porous ZnO nanocubes derived from MOF described in Comparative Example 1;

[0033] Figure 5 The gas-sensitive performance diagrams of the MOF-derived porous ZnO nanocube assembled fibers or ZnO nanocubes described in Examples 1-5 and Comparative Example 1, wherein (a) is the sensitivity of the MOF-derived porous ZnO nanocube assembled fibers described in Example 3 and the MOF-derived ZnO nanocubes described in Comparative Example 1 to various organic pollutants at 350°C and 50ppm, (b) is a sensitivity comparison diagram of the MOF-derived porous ZnO nanocube assembled fibers described in Examples 1-5 and the MOF-derived ZnO nanocubes described in Comparative Example 1 to 50ppm n-butanol at different temperatures, and (c) is a multiple cycle test curve diagram of the MOF-derived porous ZnO nanocube assembled fibers described in Example 3 to n-butanol at 350°C and 50ppm. DETAILED DESCRIPTION

[0034] Hereinafter, the present invention will describe the technical solution in detail through specific embodiments, but it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.

[0035] Example 1

[0036] This embodiment provides a MOF-derived porous ZnO nanocube assembled fiber, and the preparation method thereof is as follows:

[0037] (1) 4.54 g of 2-methylimidazole was dissolved in 70 mL of deionized water and stirred at room temperature for 40 min to obtain solution A; 0.297 g of zinc nitrate hydrate and 0.004 g of hexadecyltrimethylammonium bromide (CTAB) were dissolved in 10 mL of deionized water, stirred at room temperature for 20 min, and then ultrasonicated for 20 min to obtain solution B; solution B was quickly poured into solution A, stirred at room temperature for 40 min, and the resulting reaction solution was transferred to a centrifuge tube and centrifuged at 6500 rpm for 2 min, washed with ethanol 3 times, and washed with N,N-dimethylformamide (DMF) 3 times until the supernatant was colorless and transparent, and dried at 60°C under vacuum overnight to obtain ZIF-8 nanocubes;

[0038] (2) dispersing 0.08 g of the above-mentioned ZIF-8 nanocubes into 0.8 mL of DMF, adding 0.08 g of polyacrylonitrile, stirring at room temperature for 12 h to mix, and preparing a precursor spinning solution; using electrospinning technology, spinning the precursor spinning solution under the conditions of an ambient relative humidity of 30%, a spinning voltage of 15 kV, a push injection speed of 0.0004 mm / s, and a distance between the needle tip and the collector of 15 cm to obtain a precursor fiber;

[0039] (3) The precursor fiber is calcined in air, first at 250°C for 60 min, then at 550°C for 60 min, with a heating rate of 2°C / min. After cooling to room temperature, the MOF-derived porous ZnO nanocube assembled fiber is obtained, referred to as ZnO NFs-1.

[0040] Example 2

[0041] This embodiment provides a MOF-derived porous ZnO nanocube assembled fiber, and the preparation method thereof is as follows:

[0042] (1) Prepare ZIF-8 nanocubes according to the method described in Example 1;

[0043] (2) dispersing 0.12 g of the above-mentioned ZIF-8 nanocubes into 0.8 mL of DMF, adding 0.08 g of polyacrylonitrile, stirring at room temperature for 12 h to mix, and preparing a precursor spinning solution; using electrospinning technology, spinning the precursor spinning solution under the conditions of an ambient relative humidity of 30%, a spinning voltage of 15 kV, a push injection speed of 0.0004 mm / s, and a distance between the needle tip and the collector of 15 cm to obtain a precursor fiber;

[0044] (3) The precursor fiber is calcined in air, first at 250°C for 60 min and then at 550°C for 60 min, with a heating rate of 2°C / min. After cooling to room temperature, the MOF-derived porous ZnO nanocube assembled fibers are obtained, referred to as ZnO NFs-2.

[0045] Example 3

[0046] This embodiment provides a MOF-derived porous ZnO nanocube assembled fiber, and the preparation method thereof is as follows:

[0047] (1) Prepare ZIF-8 nanocubes according to the method described in Example 1;

[0048] (2) dispersing 0.16 g of the above-mentioned ZIF-8 nanocubes into 0.8 mL of DMF, adding 0.08 g of polyacrylonitrile, stirring at room temperature for 12 h to mix, and preparing a precursor spinning solution; using electrospinning technology, spinning the precursor spinning solution under the conditions of an ambient relative humidity of 30%, a spinning voltage of 15 kV, a push injection speed of 0.0004 mm / s, and a distance between the needle tip and the collector of 15 cm to obtain a precursor fiber;

[0049] (3) The precursor fiber is calcined in air, first at 250°C for 60 min and then at 550°C for 60 min, with a heating rate of 2°C / min. After cooling to room temperature, the MOF-derived porous ZnO nanocube assembled fibers are obtained, referred to as ZnO NFs-3.

[0050] Example 4

[0051] This embodiment provides a MOF-derived porous ZnO nanocube assembled fiber, and the preparation method thereof is as follows:

[0052] (1) Prepare ZIF-8 nanocubes according to the method described in Example 1;

[0053] (2) dispersing 0.20 g of the above-mentioned ZIF-8 nanocubes into 0.8 mL of DMF, adding 0.08 g of polyacrylonitrile, stirring at room temperature for 12 h to mix, and preparing a precursor spinning solution; using electrospinning technology, spinning the precursor spinning solution under the conditions of an ambient relative humidity of 20%, a spinning voltage of 20 kV, a push injection speed of 0.0001 mm / s, and a distance between the needle tip and the collector of 20 cm to obtain a precursor fiber;

[0054] (3) The precursor fiber is calcined in air, first at 250°C for 60 min and then at 500°C for 100 min, with a heating rate of 1°C / min. After cooling to room temperature, the MOF-derived porous ZnO nanocube assembled fibers are obtained, referred to as ZnO NFs-4.

[0055] Example 5

[0056] This embodiment provides a MOF-derived porous ZnO nanocube assembled fiber, and the preparation method thereof is as follows:

[0057] (1) Prepare ZIF-8 nanocubes according to the method described in Example 1;

[0058] (2) dispersing 0.24 g of the above-mentioned ZIF-8 nanocubes into 0.8 mL of DMF, adding 0.08 g of polyacrylonitrile, stirring at room temperature for 12 h to mix, and preparing a precursor spinning solution; using electrospinning technology, spinning the precursor spinning solution under the conditions of an ambient relative humidity of 40%, a spinning voltage of 10 kV, a push injection speed of 0.001 mm / s, and a distance between the needle tip and the collector of 10 cm to obtain a precursor fiber;

[0059] (3) The precursor fiber is calcined in air, first at 250°C for 60 min and then at 600°C for 40 min, with a heating rate of 5°C / min. After cooling to room temperature, the MOF-derived porous ZnO nanocube assembled fibers are obtained, referred to as ZnO NFs-5.

[0060] Comparative Example 1

[0061] This comparative example provides a MOF-derived porous ZnO nanocube, the preparation process of which is as follows:

[0062] (1) Prepare ZIF-8 nanocubes according to the method described in Example 1;

[0063] (2) calcining the ZIF-8 nanocubes in air, first at 250° C. for 60 min, then at 550° C. for 60 min, with a heating rate of 2° C. / min, and cooling to room temperature to obtain the MOF-derived porous ZnO nanocubes, referred to as ZnO NCs;

[0064] Comparative Example 2

[0065] This comparative example proposes a porous ZnO nanofiber, and its preparation method is as follows:

[0066] (1) adding 0.446 g of zinc nitrate hydrate to 4.5 mL of DMF, ultrasonicating for 10 min, stirring for 10 min, adding 0.9 g of polyvinyl pyrrolidone, and stirring for 8 h at a rotation speed of 120 rpm to obtain a precursor spinning solution;

[0067] (2) using electrospinning technology, spinning the above-mentioned precursor spinning solution under the conditions of an ambient relative humidity of 30%, a spinning voltage of 15 kV, a push injection speed of 0.0004 mm / s, and a distance between the needle tip and the collector of 15 cm to obtain a precursor fiber;

[0068] (3) The precursor fibers were calcined in air, first at 250°C for 60 min and then at 550°C for 60 min, with a heating rate of 2°C / min. After cooling to room temperature, porous ZnO nanofibers were obtained.

[0069] Comparative Example 3

[0070] This comparative example provides a MOF-derived porous ZnO nanocube assembled fiber, and the preparation method thereof is as follows:

[0071] (1) Prepare ZIF-8 nanocubes according to the method described in Example 1;

[0072] (2) dispersing 0.16 g of the above-mentioned ZIF-8 nanocubes into 0.8 mL of DMF, adding 0.08 g of polyvinyl pyrrolidone, and stirring at room temperature for 12 h to prepare a precursor spinning solution; using electrospinning technology, spinning the precursor spinning solution under the conditions of an ambient relative humidity of 30%, a spinning voltage of 15 kV, a push injection speed of 0.0004 mm / s, and a distance between the needle tip and the collector of 15 cm to obtain a precursor fiber;

[0073] (3) The precursor fiber is calcined in air, first at 250°C for 60 min, then at 550°C for 60 min, with a heating rate of 2°C / min. After cooling to room temperature, the MOF-derived porous ZnO nanocube assembled fiber is obtained.

[0074] The MOF-derived porous ZnO nanocube assembled fibers prepared in Example 3 and the MOF-derived porous ZnO nanocubes prepared in Comparative Example 1 were examined by scanning electron microscopy before and after calcination. The results are as follows: Figure 1 As shown, Figure 1 (a) is the morphological characteristics of the MOF-derived porous ZnO nanocubes before calcination in Comparative Example 1, which are cubic in shape, smooth in surface, uniform in particle size, and controlled at about 350 nm; Figure 1 (b) is the morphological characteristics of the porous ZnO nanocubes derived from MOF in Comparative Example 1 after calcination, which is a porous ZnO nanocube, the particle size of which is reduced to about 300 nm relative to before calcination, and the surface is rough and porous; Figure 1 (c) is the morphological characteristics of the MOF-derived porous ZnO nanocube assembled fibers before calcination described in Example 3, referring to Figure 1 (c) It can be seen that the porous ZnO nanocube assembled fiber in Example 3 has a smooth surface structure before calcination, with a diameter of about 4 μm, and it can be clearly seen that it is composed of many ZIF-8 nanocubes evenly arranged and connected together to form nanofibers; Figure 1 (d) is the morphological characteristics of the MOF-derived porous ZnO nanocube assembled fibers after calcination as described in Example 3, referring to Figure 1(d) It can be seen that the porous ZnO nanocube assembled fibers described in Example 3 are metal organic framework-derived tightly arranged and interconnected porous ZnO nanocube assembled fibers after calcination, and the fiber diameter is reduced to about 1.2 μm after calcination. The ZnO nanocube assembled fibers are composed of multiple porous ZnO nanocubes uniformly arranged into a mesh fiber.

[0075] The MOF-derived porous ZnO nanocube assembled fibers prepared in Examples 1-5 were examined by scanning electron microscopy. Figure 2 shown. Figure 2 The scanning electron microscope image of the porous ZnO nanocube assembled fiber described in Examples 1-5 of the present invention is shown in FIG. Figure 2 It can be seen that the MOF-derived porous ZnO nanocube assembled fibers described in Examples 1-5 are composed of multiple porous ZnO nanocubes uniformly arranged into a mesh fiber.

[0076] X-ray single crystal powder diffraction was performed on the MOF-derived porous ZnO nanocube assembled fibers prepared in Examples 1-4 and the MOF-derived porous ZnO nanocube prepared in Comparative Example 1. The results are as follows: Figure 3 As shown, Figure 3 X-ray single crystal powder diffraction patterns of porous ZnO nanocube assembled fibers or porous ZnO nanocubes derived from MOF in Examples 1-4 and Comparative Example 1, refer to Figure 4 It can be seen that the peak of the obtained product is consistent with the peak of ZnO (PDF#36-1451), which clearly shows that the obtained product is the metal organic framework-derived porous ZnO nanofibers that are tightly arranged and interconnected.

[0077] The specific surface area of ​​the MOF-derived porous ZnO nanocube assembled fibers prepared in Example 3 was tested and analyzed. Figure 4 (a) is a graph showing the specific surface area of ​​MOF-derived porous ZnO nanocube assembled fibers described in Example 3, referring to Figure 4 (a) It can be seen that the specific surface area is 30.9778m 2 / g, the material with large specific surface area is conducive to the adsorption and desorption of n-butanol gas, showing the characteristics of type IV adsorption isotherm with H3 hysteresis loop, and most of the pore sizes are about 30nm; Figure 4 (b) is a pore size test diagram of the MOF-derived porous ZnO nanocube assembled fibers described in Example 3, referring to Figure 4 (b) It can be seen that most of the pores are approximately 30 nm in diameter.

[0078] Performance Test:

[0079] The MOF-derived porous ZnO nanocube assembled fibers prepared in Examples 1-5 were adhered to the surface of a ceramic sheet with deionized water, and after the material was dried, a gas sensor device of metal-organic framework-derived tightly arranged and interconnected porous ZnO nanofibers with different ZIF-8 nanocube addition amounts was obtained; the MOF-derived porous ZnO nanocubes prepared in Comparative Example 1 were dispersed in ethanol / deionized water, ultrasonicated for 20 minutes, 2 μL of the dispersed liquid was dropped on a ceramic sheet, and dried at room temperature overnight to obtain a porous ZnO nanocube gas sensor device.

[0080] The gas-sensitive device was subjected to a gas-sensitive test, a picoammeter was connected to apply a 5V bias voltage to the material, and a voltmeter was connected to control the temperature.

[0081] At 350℃, 50ppm of various organic pollutant gases were introduced for testing. The results are as follows: Figure 5 As shown in (a), Figure 5 (a) The sensitivity of the MOF-derived porous ZnO nanocube assembled fibers described in Example 3 and the MOF-derived ZnO nanocubes described in Comparative Example 1 to various organic pollutants at 350°C and 50 ppm, referring to Figure 5 (a) It can be seen that compared with the MOF-derived ZnO nanocubes obtained in Comparative Example 1, the MOF-derived porous ZnO nanocube assembled fibers obtained in Example 3 have higher sensitivity to 50 ppm of various volatile organic pollutants at 350°C, and this material can improve the gas-sensing performance of various gases.

[0082] At 250-450°C, 50 ppm n-butanol was introduced for testing. The results are as follows: Figure 5 As shown in (b), Figure 5 (b) is a comparison of the sensitivity of the MOF-derived porous ZnO nanocube assembled fibers described in Examples 1-5 and the MOF-derived ZnO nanocubes described in Comparative Example 1 to 50 ppm n-butanol at different temperatures, see Figure 5 (b) It can be seen that the MOF-derived porous ZnO nanocube assembled fibers obtained in Example 3 have the highest sensitivity to 50 ppm n-butanol at 350°C.

[0083] The MOF-derived porous ZnO nanocube assembled fibers obtained in Example 3 were subjected to multiple cycle tests at 350°C and 50 ppm n-butanol. The results are as follows: Figure 5 (c) Figure 5 (c) is a graph showing multiple cycles of testing the MOF-derived porous ZnO nanocube assembled fibers at 350°C and 50 ppm of n-butanol, see Figure 5 (c) It can be seen that the MOF-derived porous ZnO nanocube assembled fibers prepared in Example 3 have good reproducibility.

[0084] Under the same conditions, the porous ZnO nanofibers or porous ZnO nanocube assembled fibers described in Comparative Examples 2 and 3 were made into gas sensing devices and then subjected to gas sensing tests. Their sensitivity to n-butanol was far less than that of the porous ZnO nanocube assembled fibers described in Example 3.

[0085] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing MOF-derived porous ZnO nanocube assembled fibers, characterized in that: The steps include: S1, preparation of ZIF-8 nanocubes; S2, electrospinning the ZIF-8 nanocubes to obtain precursor fibers; S3, calcining the precursor fiber to obtain the MOF-derived porous ZnO nanocube assembled fiber.

2. The method for preparing MOF-derived porous ZnO nanocube assembled fibers according to claim 1, characterized in that: Step S1 specifically comprises: adding hexadecyltrimethylammonium bromide and zinc nitrate into water and dispersing them uniformly, and then adding them into an aqueous solution of 2-methylimidazole to react at room temperature, thereby obtaining the ZIF-8 nanocubes; Preferably, the molar ratio of hexadecyltrimethylammonium bromide, zinc nitrate and 2-methylimidazole is 0.01:0.5-2:40-70.

3. The method for preparing the MOF-derived porous ZnO nanocube assembled fibers according to claim 1 or 2, characterized in that: The particle size of the ZIF-8 nanocubes is 250-300 nm.

4. The method for preparing the MOF-derived porous ZnO nanocube assembled fibers according to any one of claims 1 to 3, characterized in that: Step S2 specifically includes: adding the ZIF-8 nanocubes and polyacrylonitrile into an organic solvent and dispersing them evenly, and then performing electrostatic spinning to obtain the precursor fiber; Preferably, the organic solvent is N,N-dimethylformamide or tetrahydrofuran.

5. The method for preparing MOF-derived porous ZnO nanocube assembled fibers according to claim 4, characterized in that: The mass ratio of the ZIF-8 nanocubes to polyacrylonitrile is 1:1-3; Preferably, the ZIF-8 nanocubes are dispersed in an organic solvent at a concentration of 0.1-0.3 g / mL.

6. The method for preparing the MOF-derived porous ZnO nanocube assembled fibers according to any one of claims 1 to 5, characterized in that: In step S2, in the electrospinning, the needle tube advancing speed is 0.0001-0.001 mm / s, the distance between the needle tip and the collector is 10-20 cm, the spinning voltage is 10-20 kV, and the relative humidity of the environment is 20-40% RH.

7. The method for preparing the MOF-derived porous ZnO nanocube assembled fibers according to any one of claims 1 to 6, characterized in that: In step S3, during the calcination treatment, the calcination temperature is 500-600°C, the time is 40-100 min, and the heating rate is 1-5°C / min.

8. A MOF-derived porous ZnO nanocube assembled fiber, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the MOF-derived porous ZnO nanocube assembled fibers according to claim 8 in a gas sensor.

10. The use of the MOF-derived porous ZnO nanocube assembled fibers in a gas sensor according to claim 9, characterized in that: The gas sensor is used to detect n-butanol.

Citation Information

Patent Citations

  • Preparation method of bead-chain-shaped CuMn2o4 / ZnO composition fiber and obtained product

    CN107557908A

  • In-situ MOF stereocomplex polylactic acid micro / nano fiber self-powered filter membrane and preparation method thereof

    CN116726729A

  • Electrostatic spinning nano-composite electrode and preparation method and application thereof

    CN117430211A

  • Nitrogen-doped multi-layer porous carbon material as well as preparation method and application thereof

    CN118763236A